STRATEGIC PRIORITIES FOR THE TRANSFORMATION OF THE REGIONAL ECONOMIC SECURITY SYSTEM UNDER WAR CONDITIONS AND DURING THE POST-WAR RECONSTRUCTION STAGE - SIUTA, Sviatoslav (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The study analyzes the issues of managing the economic security of a region. The purpose of the article is to substantiate the strategic priorities of transforming the system of economic security of the region under the conditions of war and at the stage of post-war reconstruction. It is shown that the turbulence and deepening parameters of uncertainty in the development of socio-economic relations require substantiation of the targeted strategic priorities for the transformation of the regional economic security system, taking into account the challenges of the legal regime of martial law and the prerequisites for the necessity of Ukraine’s post-war reconstruction. Structural gaps in ensuring economic security at the regional level have been identified. The following strategic priorities of the transformation of the regional economic security system are determined: improvement of the institutional basis for guaranteeing the protection of the state’s economic interests at the regional level; enhancement of the investment attractiveness of the region; stimulation of the innovation and technological component of economic security; development of the military-industrial and defense sector in the regions; balancing the processes of specialization and diversification of entrepreneurial activity in the region, taking into account the available natural-resource potential and the established traditions of economic management; stabilization of negative demographic processes and development of human capital. It is argued that the system of economic security of the region plays a strategically important role in ensuring the diversification of risks in the regional dimension, in leveling the disproportions of the spatial and territorial development of the state, and in overcoming the striking disparity of incomes between the rural and urban population.
Keywords: region; regional policy; regional economy; economic security; system; challenges; threats; strategic priorities; transformation